The pursuit of a more powerful thermodynamic hydrate inhibitor than methanol. Dimethyl sulfoxide as a case study - Semenov A.P.; Mendgaziev R.I.; Stoporev A.S.; Istomin V.A.; Sergeeva D.V.; Ogienko A.G.; Vinokurov V.A. (2021)
Search for new, more effective hydrate formation inhibitors is one of the oil and gas industry's urgent tasks. Dimethyl sulfoxide (DMSO) can be considered as a promising anti-hydrate reagent. DMSO and its aqueous solutions were characterized by several physicochemical methods, including measuring their density, viscosity, freezing point, the methane hydrate equilibrium conditions (V-Lw-H), and identification of the hydrate type formed. The hydrate phase equilibria in the system of DMSO aqueous solution–gaseous methane were determined for a wide range of DMSO concentrations (0–55 mass%), temperatures (242–289 K), and pressures (3–13 MPa). X-ray measurements reveal that DMSO does not form double hydrate with methane over the entire concentration range. The data obtained show that DMSO is a thermodynamic hydrate inhibitor. To quantitatively describe the anti-hydrate activity of DMSO, a correlation of thermodynamic depression ΔTh with the mass fraction of DMSO in solution and gas pressure was proposed. It was found that at concentrations above 33 and 53 mass% DMSO becomes more effective THI than the widely used monoethylene glycol and methanol, respectively. Such behavior is associated with the greater non-ideality of DMSO aqueous solutions (negative deviations from Raoult's law) compared to alcohols aqueous solutions. A linear correlation linking the depression of hydrate equilibrium temperature ΔTh and ice freezing point ΔTice was also derived. A comparative analysis of the density and kinematic viscosity of aqueous solutions of DMSO and methanol (0–100 mass%) was performed. It was revealed that DMSO is a promising inhibitor combining high anti-hydrate activity, low volatility (compared to methanol), and acceptable viscosity properties of aqueous solutions.